Transforming Argumentative Writing Skills Through Project-Based Learning Implementation In Indonesian Language Subjects - Murny Murny; Fitra Herlinda; Nurhasnawati Nurhasnawati; Martius Martius; Ripi Hamdani (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This research was motivated by the low argumentative writing skills of students, which resulted from learning models that were insufficiently innovative and failed to optimally engage students. Argumentative writing skills represent complex productive competencies that cannot be mastered independently but require consistent practice and exercise. This study aims to transform students' argumentative writing skills through the implementation of a project-based learning model in Indonesian language subjects. This research employed a classroom action research method following the Kemmis and McTaggart model, conducted over two cycles, with 32 eighth-grade junior high school students as research subjects. Data collection instruments included argumentative text writing tests, observation sheets, and field notes. Data analysis was performed using descriptive quantitative and qualitative methods. The findings revealed a significant transformation in students' argumentative writing skills following the implementation of the project-based learning model. In Cycle I, the average student score reached 72.5 with a mastery percentage of 62.5%, while in Cycle II, the average score increased to 83.4 with a mastery percentage of 87.5%. This improvement was also evident across aspects of text structure, paragraph coherence, diction, and spelling. This study concludes that the project-based learning model effectively transforms students' argumentative writing skills.